The Relation between Lipid Profile and Glycemic Control in Type 2 Diabetes Mellitus Patients in North Sumatera, Indonesia - Rusdiana, Rusdiana; Widjaja, Sry Suryani; Savira, Maya (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: The global prevalence of type 2 diabetes mellitus (DM), a chronic metabolic disorder, has been steadily increasing. Increasing blood sugar levels (BSL) are reliably measured by glycated hemoglobin (HbA1c). AIM: The aim of this research is to observe the relation between lipid profile with glycemic control at uncontrolled and controlled type 2 DM, early detection of abnormalities in the lipid profile can minimize cardiovascular complication risk in patients with type 2 DM. METHODS: Collecting medical data record, for example, blood pressure, height and body mass index, duration of disease, family history, and medicine treatment. Laboratory examination such as BSL, HbA1c levels, and lipid profile such as cholesterol, low-density lipoprotein, high-density lipoprotein, and triglycerides (TGs) was evaluated. The study was conducted by implementing cross-sectional methods, among 112 patients with type 2 DM who were admitted from various primary health-care centers in Medan city and the surrounding areas in North Sumatera. The sample criteria are type 2 DM’ patients and both genders. The exclusion criteria of the samples are those with type 1 DM and critical disease. RESULTS: There is a difference between the average lipid profile level (high-density lipoprotein and TG) in controlled and uncontrolled type 2 DM. Furthermore, there is also a difference between the average HbA1c value in controlled type 2 DM and uncontrolled type 2 DM (p<0.005). CONCLUSION: This study showed a difference in lipid profile (high-density lipoprotein and TG) and HbA1c between uncontrolled and controlled type 2 DM. Therefore, type 2 DM patients were recommended to undergo periodical glycemic and lipid profile examination control to prevent cardiovascular disease complication.